Giant Glycosidase Inhibitors: First‐ and Second‐Generation Fullerodendrimers with a Dense Iminosugar Shell. Issue 10 (25th January 2018) - Nierengarten, Jean‐François; Schneider, Jérémy P.; Trinh, Thi Minh Nguyet; Joosten, Antoine; Holler, Michel; Lepage, Mathieu L.; Bodlenner, Anne; García‐Moreno, M. Isabel; Ortiz Mellet, Carmen; Compain, Philippe
Abstract: The multivalent effect in glycosidase inhibition is a new topic in glycoscience that has emerged a few years ago, with the discovery of neoglycoclusters displaying strong binding enhancements over the corresponding monovalent inhibitor. Iminosugar–fullerene conjugates with high valencies have been prepared from iminosugar‐terminated dendrons and a clickable fullerene hexa‐adduct scaffold. The simultaneous grafting of twelve dendrons allows for a very fast dendritic growth thus limiting the number of synthetic steps required to prepare compounds with a high number of peripheral units. The grafting of first‐ and second‐generation dendrons provided fullerodendrimers surrounded by 36 and 108 peripheral iminosugars, respectively. Inhibition studies have been carried out with a panel of glycosidases. In the particular case of Jack bean α‐mannosidase, the 108‐valent nanoconstruct displays inhibition in the nanomolar range and an additional binding enhancement of one order of magnitude when compared to the 36‐valent analogues. Abstract : Giant sugar trees : Iminosugar–fullerene conjugates with high valencies have been prepared from iminosugar‐terminated dendrons and a clickable fullerene hexa‐adduct scaffold. The 108‐valent fullerodendrimer (see figure) displayed α‐mannosidase inhibition in the nanomolar range and an additional enhancement of one order of magnitude when compared to the corresponding 36‐valent first‐generation dendrimer.